Birth-related characteristics predict vision-related quality of life in adults: A population-based study - Jannet Philip; Frouke N. Boonstra; Bianca Huurneman; Nomdo M. Jansonius (PLoS ONE, 2026)
Background Individuals with an abnormal birth are at risk of having ophthalmic complications and visual impairment. The aim of this study was to understand the relationship between birth-related characteristics and vision-related quality of life (VR-QoL) in adults in the general population. Methods We used data from Lifelines, a population-based cohort study from the North of Netherlands (n = 167,000). We included individuals with National Eye Institute Visual Function Questionnaire 25 (NEI-VFQ-25) data (n = 29,840; 18–55 years). Included birth-related characteristics were gestation length, birth weight, mode of delivery, and the presence of birth defects. We used ordinal regression with the NEI-VFQ-25 items as dependent variable and the birth-related characteristics as independent variables. Analyses were adjusted for age and gender, and corrected for multiple hypothesis testing using false discovery rate (FDR). Results Participants with birth defects directly related to eye or brain development showed a poor VR-QoL in 9/10 subscales (FDR-corrected P value q < 0.001 to 0.05) with the most pronounced effect for difficulties performing peripheral vision-related activities. Individuals with birth defects not directly related to eye or brain development showed a poor VR-QoL in 4/10 subscales (q = 0.02 to 0.05). Early preterm birth was related to the general vision (q = 0.02) and vision specific social functioning (q = 0.05) subscales. High birth weight (>4500 g) contributed to general vision problems (q = 0.05), and vacuum or forceps mode of delivery was associated with difficulties performing activities under low luminance conditions (q = 0.02). Conclusion At the level of the general population, birth-related characteristics are related to VR-QoL. To elucidate the underlying mechanisms, future studies could add visual function to the questionnaire outcomes.